Electroluminescent film time control system - Loi, Hui Ying. (2009)
Electroluminescence is a phenomenon that generates light through the use of electricity into a phosphor. To create the light, an inverter circuit based on a half-bridge configuration that allows the interchanging of polarity in the electroluminescent film is used.